2019
DOI: 10.3390/antiox8050142
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and a Reliable Method to Quantify Antioxidant Activity In Vivo

Abstract: The characterization of compounds with antioxidant activity is of great interest due to their ability to reduce reactive oxygen species production and, therefore, prevent some age-related diseases. Its antioxidant capacity can be analyzed by different methods both in vitro and in vivo. Caenorhabditis elegans is an in vivo model widely used in ageing research. Until now, available tests analyze functional effects in the worms, so the antioxidant activity of the compound is indirectly monitored. We have develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 30 publications
0
54
0
Order By: Relevance
“…First, in vitro antioxidant activities were investigated in a DPPH radical scavenging assay, which is regarded as the first approach for evaluating antioxidant activity due its simplicity, speed, and low cost. 31 In principle, the hydrogen-donating ability of antioxidants reduces the free radical DPPH · (purple) to a stable DPPH (yellow), leading to decreased absorbance at 517 nm. 32 As shown in Figure 3 , various concentrations of each sample (samples 1–3) were tested to measure their DPPH radical scavenging activities.…”
Section: Resultsmentioning
confidence: 99%
“…First, in vitro antioxidant activities were investigated in a DPPH radical scavenging assay, which is regarded as the first approach for evaluating antioxidant activity due its simplicity, speed, and low cost. 31 In principle, the hydrogen-donating ability of antioxidants reduces the free radical DPPH · (purple) to a stable DPPH (yellow), leading to decreased absorbance at 517 nm. 32 As shown in Figure 3 , various concentrations of each sample (samples 1–3) were tested to measure their DPPH radical scavenging activities.…”
Section: Resultsmentioning
confidence: 99%
“…We employed the DPPH and ABTS+ radical scavenging methods to investigate the antioxidant activity of plant extracts that showed antiviral potency. The DPPH method is based on the reduction in a stable electron/hydrogen acceptor, which is reduced to DPPH [ 80 ], while a cation ABTS+ reacts with antioxidants by an electron transfer mechanism [ 81 ]. In our study, evaluation of the DPPH and ABTS+ scavenging activity showed approximately similar values, which suggests that these two methods are positively correlated.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, measurements of the in-vitro AOP of extracts/ compounds can be used as a first screening to help to define them as extracts/ compounds with potential antioxidant activity before the use of in-vivo models. However, while in-vitro tests are used to demonstrate the intrinsic activities of the compounds, in-vivo assays are focused on the physiological effects, to provide a second, and essential, line of evidence for antioxidant activity [28,29].…”
Section: Discussionmentioning
confidence: 99%